2019
DOI: 10.1111/vco.12473
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal transcriptomic and genetic landscape of radiotherapy response in canine melanoma

Abstract: Canine malignant melanoma (MM) is a highly aggressive tumour with a low survival rate and represents an ideal spontaneous model for the human counterpart. Considerable progress has been recently obtained, but the therapeutic success for canine melanoma is still challenging. Little is known about the mechanisms beyond pathogenesis and melanoma development, and the molecular response to radiotherapy has never been explored before. A faster and deeper understanding of cancer mutational processes and developing me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…Nevertheless, taking into account the MI and the tumour location, the CFA 30 amplification was not any more significant, probably because of its strong association with the MI. Indeed, genes lying on this recurrent amplified region probably bring an advantage for the proliferation and progression of the tumour, such as TRPM7 involved in the MAPK pathway . Focal amplifications along CFA 10 were often found in two distinct regions covering the targeted genes MDM2 and the cycline‐dependent‐kinase CDK4 , and this association was demonstrated in a previous study .…”
Section: Discussionsupporting
confidence: 51%
“…Nevertheless, taking into account the MI and the tumour location, the CFA 30 amplification was not any more significant, probably because of its strong association with the MI. Indeed, genes lying on this recurrent amplified region probably bring an advantage for the proliferation and progression of the tumour, such as TRPM7 involved in the MAPK pathway . Focal amplifications along CFA 10 were often found in two distinct regions covering the targeted genes MDM2 and the cycline‐dependent‐kinase CDK4 , and this association was demonstrated in a previous study .…”
Section: Discussionsupporting
confidence: 51%
“…MDM2 (8,27,28), CDK4 (8,28), and CDKN2A (24,27,28), which were found altered by other authors, were not identified as significantly aberrated by GISTIC algorithm in…”
Section: Discussionmentioning
confidence: 68%
“…The syntenic human regions were then compared with published data (5,7,8,24), to detect those regions shared by both hMMs and COMs. A comparative analysis between data produced herein, and recently published studies regarding the detection of CNAs in the canine genome through several techniques (as WES, WGS, aCGH, and FISH) (8,24,27,28), was also performed.…”
Section: Comparison Between Canine and Human Cnasmentioning
confidence: 99%
See 2 more Smart Citations